Connecting - Christy Wenger; Christina Martorana; Jacquelyn E. Hoerman-Elliot; Beth Godbee; Adrianne Wojcik; Laurence Musgrove (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
Christy Wenger - Risks and Rewards of Purposeful Vulnerability Christina Martorana - Embracing Vulnerability in Teaching Jacquelyn E. Hoerman-Elliott - Writing as a Sea of Oms: A “This I Believe” Essay for Contemplative Writing in First-Year Composition Beth Godbee and Adrianne Wojcik - Decoding Each Other through Coding: Sharing Our Unlikely Research Collaboration Laurence Musgrove - Dress Up Laurence Musgrove - Trees